Evaluation of Some Commercially Available Insecticides against Mango Leaf Gall Midge Procontarinia matteiana (Diptera: Cecidomyiidae) - Tirthankar Dalui (New Visions in Biological Science Vol. 4, 2021)
India is the world’s largest mango producer, but it has the lowest productivity among the top five countries. Pest complexes that damage fruits, flowers, stems, and leaves are one of the most serious issues confronting the mango industry. Mango is attacked by over 400 pests worldwide. Many Cecidomyiidae species, particularly those of the genus Procontarinia, attack mango leaves. Procontarinia matteiana (Kieffer & Cecconi) is the most common and widespread species, and it is a well-known pest of mango in Asia and Africa. The adult midge is a minute fly that dies after copulation and oviposition within 24 hours of emergence. On the leaves, there are small wart-like galls. Heavily galled leaves curl up and drop prematurely. As a result, it reduces photosynthesis efficiency and disrupts the tree’s normal physiological activity, resulting in lower mango fruit yields. As a result, a study was conducted on selected uniform plants (cv. Himsagar) at a private orchard in Chhotajagulia, North 24 Parganas, West Bengal, India, to evaluate the bioefficacy of new insecticide mixtures along with conventional insecticides against mango leaf gall midge in two consecutive seasons (2017-18). The objective of the study is to expedite the bioefficacy of different newly introduced insecticides and insecticidal modules along with conventional insecticides and biopesticides for effective management of mango leaf gall midges. The investigation was undertaken in a randomised block design, with three replications of each treatment and an untreated water spray check. The experiment consisted of eight treatments, including the control. Five hundred leaves were chosen at random from a branch to examine and calculate the percentage of newly formed and mature galls on fresh leaves. At weekly intervals, the damage was assessed by counting total leaves versus infested leaves. According to the results of the study, the combination of beta-cyfluthrin 9% +imidacloprid 21% 300 OD@ 75 g a.i/ha was the most effective to reduce leaf gall infestation, followed by thiamethoxam 12.6% + lambda cyhalothrin 9.5% 247 ZC @ 22 g a.i/ha.